2014
DOI: 10.1093/jac/dku470
|View full text |Cite
|
Sign up to set email alerts
|

Virological failure after 1 year of first-line ART is not associated with HIV minority drug resistance in rural Cameroon 

Abstract: Virological failure after 1 year of ART was not associated with minority drug resistance at baseline but with incomplete adherence. Strategies to assure adherence and uninterrupted drug supplies are pivotal factors for therapy success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Kyeyune et al, reported the presence of DRMs in low frequency only for 65% of Ugandan patients failing cART [45]. However, in other studies no association between VF and the presence of low-frequency drug resistant variants was observed[46, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…Kyeyune et al, reported the presence of DRMs in low frequency only for 65% of Ugandan patients failing cART [45]. However, in other studies no association between VF and the presence of low-frequency drug resistant variants was observed[46, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…The variation in proportion of patients failing first-line ART observed in the field is remarkably high and variable, ranging from 8 to 16.9% in Africa [11][12][13][14][15][16][17][18][19] and from 8.9 to 13% elsewhere [20][21][22]. The few retrospective studies conducted at Accredited HIV Care Center (AHCC) in the Northwest, Southwest and Littoral regions of Cameroon have shown treatment failure on first-line ART between16 and 23.2% [2,[23][24][25]. The rate of patients switching to second-line ART also varies and ranged from 3.5 to 30% in Africa [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In the reference HIV/AIDS out‐patient clinic of the Central Hospital in Yaoundé in 2006–2009, this proportion was 77% after 24 months of ART and 82% after 36 months . In the Bamenda Regional Hospital in 2010, it was 84% after 12 months of ART . Finally, only 61% of patients had virological suppression after a median time on ART of 24 months in a district hospital located in a very remote area in northern Cameroon in 2009–2011 .…”
Section: Discussionmentioning
confidence: 99%